ETERNITY OF FOLK SONGS - Mashhura Khamidjonovna Khusanova (Journals Park Publishing, 2023)
In this article, the incomparable importance of Uzbek folk songs in the heritage of our people, their role in raising the spiritual level of our people is justified.
Keywords: music, singer, song, values, traditions, spiritual heritage, national and universal values, performance art, folklore, status.